Kinetics of reduction of metal values from fayalite-based slags - part 2: modelling of idealized slag-cleaning conditions - B. S. Terry; C. L. Harris (The Institute of Materials, Minerals and Mining, 1995)
Reduction kinetics from slags containing CuO(0.5), ZnO, PbO, NiO and SnO into a Cu-based metal phase were subjected to computer simulation using a previously developed model for the kinetics of metal-slag-gas reactions that assumes mass-transfer control in all phases. The effects were examined of changing bulk Fe oxide activity, gas reducing potential, temperature, Fe content of the Cu phase and metal/slag ratio. The results permit practical conclusions to be drawn about industrial slag-cleaning practice, but the model is still limited in terms of thermodynamic inputs and the idealisation of reaction conditions